The Ca2+/CaN/ACC and cAMP/PKA/HK signal pathways are required for PBAN-mediated sex pheromone biosynthesis in Conogethes punctiferalis - Yao Zhang; Zelong She; Ruolan He; Shuangyan Yao; Xiang Li; Xiaoguang Liu; Xinming Yin; Jizhen Wei; Mengfang Du; Shiheng An (Journal of Integrative Agriculture, 2024)
Conogethes punctiferalis is a crop and fruit pest that has caused serious economic losses to agricultural production. This pest relies heavily on its sex pheromone to ensure sexual encounters and subsequent mating success. However, the molecular mechanism underlying sex pheromone biosynthesis in this species remains elusive. The present study investigated the detailed mechanism underlying PBAN-regulated sex pheromone biosynthesis in C. punctiferalis by transcriptome sequencing of the C. punctiferalis pheromone glands (PGs) and subsequent functional identification of the target genes. The results showed that female mating started from the first scotophase, and peaked at the second to fifth scotophases in accordance with the release of sex pheromones. PBAN regulated sex pheromone biosynthesis by employing Ca2+ and cAMP as secondary messengers, as demonstrated by RNA interference (RNAi), pharmacological inhibitors, and behavioral assays. Further investigation revealed that calcineurin (CaN) and acetyl-CoA carboxylase (ACC) were activated by PBAN/Ca2+ signaling, and the RNAi-mediated knockdown of CaN and ACC transcripts significantly reduced sex pheromone production, ultimately leading to a significantly reduced ability of females to attract males. Importantly, hexokinase (HK) was found to regulate sex pheromone biosynthesis in response to the PBAN/cAMP/PKA signaling pathway, as demonstrated by RNAi, enzyme activity, and pharmacological inhibitor assays. Furthermore, Far2 and Desaturase1 were found to participate in PBAN-regulated sex pheromone biosynthesis. Altogether, our findings revealed that PBAN regulates sex pheromone biosynthesis through the PBANR/Ca2+/CaN/ACC and PBANR/cAMP/PKA/HK pathways in C. punctiferalis, which enriches our comprehension of the details of sex pheromone biosynthesis in moths.